Correlations Between Estimated Pulmonary Capillary Wedge Pressure (ePCWP) and Clinical Parameters in Hemodialysis Patients: A Clinical Study in an Iranian Referral Hospital - Omidi, Fatemeh; Adman, Salahadin; Aghajani, Mohammad Haji; Nassiri, Amir Ahmad; Ahmadi Koomleh, Azadeh; Khoshdel, Nahal; Sabaghian, Tahereh (Novelty in Biomedicine, 2025)
Background: Due to fluid overload, hemodialysis patients are at a high risk of cardiovascular complications. Accurate assessment of fluid status is vital for optimal management. This study investigates correlations between Estimated Pulmonary Capillary Wedge Pressure (ePCWP) and clinical parameters in hemodialysis patients to evaluate its utility in fluid management. Materials and Methods: This clinical study included 40 hemodialysis patients from an Iranian referral hospital. Patients were selected based on strict inclusion and exclusion criteria. Data collection involved comprehensive assessments of demographic, clinical, and examination data, with baseline and post-dialysis measurements obtained. Tissue Doppler imaging and echocardiography were performed before and after dialysis, and ePCWP was calculated. Statistical analyses were conducted using IBM SPSS Statistics, version 26, to explore correlations between ePCWP, bioimpedance measures, and clinical factors. Results: Significant post-dialysis reductions were observed in systolic blood pressure (mean difference=7.25 mmHg, p<0.001), diastolic blood pressure (mean difference=4.37 mmHg, p<0.001), and weight (mean difference=2.27 kg, p<0.001), alongside a decrease in extracellular water to total body water (ECW/TBW) ratio (mean difference=0.01, p<0.001). However, no significant difference was found in ePCWP before and after dialysis (mean difference=0.881 mmHg, p=0.4). Correlation analysis revealed a moderately positive correlation between EPCWP before dialysis and ECW/TBW (r=0.359, p=0.023). However, it was not significantly correlated with blood pressure and weight. Conclusion: ePCWP demonstrates potential as a marker for fluid status in hemodialysis patients, especially in settings where bioimpedance analysis is not available. However, its clinical utility requires further validation through larger randomized controlled trials.